Pengaruh Kepemimpinan, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Matahari Department Store Cabang Festival Citylink Bandung - Wijaya, Fanji; Dameria, Oktaviani (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
PT Matahari Department Store Festival Citylink Bandung Branch has a company vision to become the best department store that is customer-centered in providing solutions to customers. However, initial interviews with company management found that employee performance still needed to be improved, and there was a need for more leadership, discipline, and aspects of the employee work environment. Thus, this research seeks to find the influence of leadership, discipline, and work environment on employee performance. This quantitative research used a sample of 60 employees as research respondents. The research results found that leadership and discipline had a significant impact on employee performance partially, but the work environment did not. Meanwhile, the results of simultaneous testing found that all three variables simultaneously significantly impacted employee performance.